Thermal analysis of a high speed electrical machine - La Rocca, Antonino (2016)
This work has analysed, designed, commissioned and validated the performance of a novel cooling system for an innovative high speed, three-phase synchronous permanent magnet machine designed for an aero-engine starter/generator with a power rating of 45 kW and maximum speed of 32,000 rpm. The cooling system designed consisted into inserting a 1 mm non-electrically conductive stator sleeve in the machine airgap, this separates the rotor region from the stationary components letting the rotor running dry at all times; the stator region can then be flooded with oil. Oil enters from one side of the machine through some radial openings impinging directly over the end-winding, it then flows through two rows of equally sized axial ducts located along the inner and outer diameter of the stator to give an even distribution of the coolant, and finally it flows over the surface of the rear end-winding and leaves the machine. The thermal modelling was carried out by the joint use of Computational Fluid Dynamics (CFD) and Lumped Parameter Thermal Network (LPTN); this allowed the investigation of heat transfer phenomena and the optimisation of the cooling design. CFD was primarily employed to investigate the fluid flow and to perform conjugate heat transfer analyses; these allowed the determination of heat transfer coefficients and the prediction of temperature distribution inside the machine. Thermal networks were developed to investigate the heat flow through machine components, to perform the design optimisation and to maximise overall machine performance. A thermal network was also developed by the author to investigate the heat transfer phenomena inside the bearing chambers. An experimental apparatus was designed and commissioned in order experimentally validate the thermal models developed. Temperatures, pressures and torque up to 20,000 rpm were recorded throughout the tests and data collected were compared to quantities predicted analytically and numerically. Maximum winding temperatures measured performing a short circuit test agree well with analytical and numerical prediction with a maximum difference of 10%; mechanical losses measured carrying out a no-load test agree well at speeds over 10,000 rpm with differences between 2 and 12%. Throughout tests, pressure drops were monitored across the machine and an agreement of 13% with prediction were achieved. Design improvements are also proposed to further enhance the cooling of stator slots and of rotor components.